Air concentrations and deposition of chlorinated dioxins and furans (PCDD/F) at three high alpine monitoring stations: Trends and dependence on air masses. (15th February 2020) - Kirchner, M.; Freier, K.P.; Denner, M.; Ratz, G.; Jakobi, G.; Körner, W.; Ludewig, E.; Schaub, M.; Schramm, K.-W.; Weiss, P.; Moche, W.
Abstract: Ambient air concentrations and bulk deposition of polychlorinated dibenzo- p -dioxins and dibenzo–furans (PCDD/F) were monitored at three high Alpine stations in Germany (Schneefernerhaus/Zugspitze: 2650 m a.s.l.), Switzerland (Weiβfluhjoch: 2663 m a.s.l.), and Austria (Sonnblick Observatory: 3106 m a.s.l.) from 2005 to 2018. High-volume active air samplers were selectively in operation on a daily basis according to predicted source-regions of air masses. Air concentrations showed only small differences between the three sites and were one or two orders of magnitude lower than in urbanized areas in central Europe. Calculation of source contribution revealed waste incineration, heating, and coal combustion as major sources of PCDD/F in ambient air. Air masses from the northeast were characterized by higher concentrations of PCDD/F than those from northwest and south. However, air masses from the northeast source region are significantly less frequent at the three Alpine stations than air masses from the other source regions. Only at Schneefernerhaus, the majority of congeners exhibit a clear decreasing temporal trend in ambient air concentrations. Deposition rates of PCDD/F measured at the three stations were almost as high as at monitoring stations in urban agglomerations. Despite lower precipitation rates in the central Alps, deposition of PCDD/F was higher at the Sonnblick Observatory than in the Northern Alps (Schneefernerhaus). Bulk deposition for Weiβfluhjoch and Schneefernerhaus exhibit a decreasing temporal trend. Highlights: Alpine concentrations of PCDD/F in ambient air distinguishing four source regions. Air concentrations 1–2 orders of magnitude lower than in urbanized European areas. Partly decreasing temporal trends of ambient air concentrations but levelling of. Deposition rates in the same order of magnitude like at urban agglomerations. Domestic heating, coal burning and waste incineration as dominant sources.